Accelerating coal plant retirement at scale - Deb Chattopadhyay; Brad Handler; Chandrasekar Govindarajalu (Asian Development Bank Institute (ADBI), 2023)
Although coal plants in some countries are actively being retired ahead of their planned closure dates, there is yet to be sufficient clarity on which business model(s) might help to achieve this at scale. Policy-based and market-led closures, buyout of coal plants, auctioning them off, repurposing them, and swapping coal assets with renewables have all been tried in different parts of the world. In this paper, we first summarize these business models and reflect briefly on the insights gained from these experiences. We then focus on the core questions: How can coal retirements be scaled up? Is there a reason that one model unilaterally works better than others? Do these models need to be crafted specifically to fit the context of each country/system? Can they be combined in some shape or form to carry out retirements at scale more efficiently? We address these issues around some of the country/utility coal fleets where the World Bank team is having active dialogues under the aegis of the Accelerating Coal Transition (ACT) program. The broad conclusions that emerge from the discussion point to the need for a tailored hybrid model that best fits the policy, system, and ownership of a coal fleet.
Keywords: Q40; Q41; Q42; 330; coal retirement; coal-fired power plants; Accelerating Coal Transition (ACT) program; energy transition mechanism; renewable energy